(3dhGRe GdbVGI hGdMcGe aj EUdGM CehQ GdCfGes - (3VMcj , eUWaj Hf eMeO Hf jGQOe Hf SQNGf GdSjQhRj,J (B1090 (3g` s
(3ChdgG (B:s
(3hHYO agPg ChQGb ecJhHI dMd eTcdGJ edJbi GdCHMQ eSJfHWI ef TQhM GdeJhf s
(3BNQgG (B:s
(3hai ZjQg ef ehVY BNQ aGcJajJ HPcQgG ai CMO GdehVYjf hGddg MSHi hfYe Gdhcjd JeJ GdcJGH s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B241 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B288s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B412s
Keywords: (3Gdabg GdMfajs